2010
DOI: 10.1242/jcs.062299
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating signal delivery – plasma-membrane ERK activation in aPKC-dependent migration

Abstract: SummaryMembers of the PKC superfamily have been implicated in various migratory models and in particular in spatially restricted processes. However, defining the precise local events that underlie the PKC-dependent processes is constrained by the unspecific nature of interventions. Here we address this problem in relation to atypical PKC (aPKC) action, which in conjunction with the exocyst complex controls the polarised delivery of promigratory signals. A drug-dependent recruitment approach was employed to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…We speculate that the ERK2-specific regulation of HGFinduced motility is due in part to specific ERK2-mediated paxillin phosphorylation, which would in turn affect focal adhesion dynamics as demonstrated in a different motility model (Boeckeler et al, 2010). Indeed we find that HGFtreatment results in an increase of the disassembly rate of paxillin-containing focal adhesions (Fig.…”
Section: Erk2 Mediates Hgf-induced Motility 2387supporting
confidence: 51%
“…We speculate that the ERK2-specific regulation of HGFinduced motility is due in part to specific ERK2-mediated paxillin phosphorylation, which would in turn affect focal adhesion dynamics as demonstrated in a different motility model (Boeckeler et al, 2010). Indeed we find that HGFtreatment results in an increase of the disassembly rate of paxillin-containing focal adhesions (Fig.…”
Section: Erk2 Mediates Hgf-induced Motility 2387supporting
confidence: 51%
“…It appears that on delivery to the leading edge dynein IC2 is involved in controlling FA turnover, phenocopying aPKC knock down and hence linking aPKC action in delivering dynein IC2 (dynein-dynactin complex) with its control of FA turnover. Because the inhibition of aPKCs triggers an increase in the FA content of another marker, zyxin (Boeckeler et al, 2010), we analysed the effects of dynein IC2 depletion on zyxin and paxillin at FAs (Fig. 3D).…”
Section: Resultsmentioning
confidence: 99%
“…3D). Because the aPKCs are important for the destabilisation of FAs (Boeckeler et al, 2010), (Rosse et al, 2009), we analysed the effect of the depletion of dynein IC2 on the disassembly rate of paxillin at FAs during cell migration using total internal reflection fluorescence (TIRF) microscopy and taking into consideration the localisation of the FAs (peripheral FA versus internal FA; Fig. 3C; supplementary material Movies 2, 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kibra scaffolds the association between aPKC and the exocyst. The aPKCs, Kibra and the exocyst are shown to be required for NRK cell migration, and it is further demonstrated that they are necessary for the localized activation of c-Jun N-terminal kinase (JNK) and extracellular-signal-regulated kinase (ERK) at the leading edge of migrating cells (Rosse et al 2009;Boeckeler et al 2010). The activation of ERK and JNK in turn mediates the phosphorylation of paxillin, a component of focal adhesion complex, which is involved in the regulation of dynamic focal adhesions.…”
Section: The Ral Gtpasesmentioning
confidence: 99%